(untitled) (Perner’s Contacts, 2022)
The market for rail services in EU countries has long been inaccessible to the private sector. Transport services were provided by national carriers, which led to the prevention of participation in fair and non-discriminatory competition in the provision of rail transport services. The main goal of customers of transport services in the public interest as well as providers of transport services is to provide transport services in the public interest and to increase the occupancy of individual connections as much as possible. The more passengers will travel on a given route, the higher the revenue the route will have and therefore it will not be necessary to require more funds from public budgets. It is necessary to analyze the overall development in the operation of rail passenger transport, including the entry of private carriers into the infrastructure of the Železnice Slovenskej republiky. Based on the knowledge of the current situation, it is necessary to take measures to achieve compliance with the requirements of Regulation (EC) 1370/2007, which is coordinated by the Ministry of Transport and Construction of Slovak Republic. The paper characterizes the current state of organizing public tenders in the Slovak Republic and their course and proposes the gradual steps of the public tender in the form of a schedule. An important point of the whole process of the organization of the public tender is the correct setting of competencies, determination of the subject of the public tender and, last but not least, to propose a uniform methodology of the public tender, which may, however, vary in individual states due to the conditions of national legislation. Part of the unified methodology is the determination of the phases of the public tender process, which are part of the schedule of the public tender. The schedule of the public tender shows the entire cycle, resp. the duration of each phase of the tender for each proposed group of measures taken.